Jamur Kontaminan Pada Umbi Kentang - Sri Rahayu; Fitri Nadifah; Yuliana Prasetyaningsih (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2015)
Potato (Solanum tuberosum L.) is one of the five basic sources of carbohydrates. It consumed by many people world spreads. One of the constraints in potato production is the presence of fungal diseases. Fungi that cause diseases in potato crops include Phytophthora infestans which causes late blight, Fusarium oxysporum which cause fusarium wilt, Alternaria solani Sor. which cause brown spot disease, and Aspergillus niger which infect bulbs and produce aflatoxin. Identification of potatoes-contaminating fungi can lead the farmers to get a better potatoes production. This research goal is to identify potatoes-contaminating fungi in traditional market of Condong Catur, District of Sleman, Yogyakarta. This research was using descriptive method with laboratory examination. We took 30 defected potatoes suspected of being infected by fungi. Samples were taken from eachpotato aseptically and then cultured in Saboraud’s Dextrose Agar (SDA) media. Observation was held for the fungi growth after 24 hours incubation. From the laboratory examination, there were fungal infections in all of potatoes and identified as Phytopthora infestans (26.67%), Fusarium oxysporum (86.67%), Alternaria solani Sor. (6.67%), and Aspergillus niger (13.33%). Phytophthora infestans, Fusarium oxysporum, Alternaria solani Sor., and Aspergillus niger identified as potatoes-contaminating fungi in Traditional Market of Condong Catur, District of Sleman, Yogyakarta.Keywords: contaminant, fungi, potatoes